Combined Therapy of Catheter Ablation and Left Atrial Appendage Closure for Patients with Atrial Fibrillation: A Case-Control Study - Bin-Feng Mo; Jian Sun; Peng-Pai Zhang; Wei Li; Mu Chen; Jia-Li Yuan; Yi Yu; Qun-Shan Wang; Yi-Gang Li (Journal of Interventional Cardiology)
Aim. The feasibility and safety of performing the combined procedure of catheter ablation (CA) and left atrial appendage closure (LAAC) for atrial fibrillation (AF) have been reported by observational studies without controls. The aim of this study was to compare the procedural and long-term outcomes of combined procedures with isolated CA or LAAC. Methods and Results. This study included patients who underwent combined CA and LAAC (combined group), CA alone (CA-only group), or LAAC alone (LAAC-only group). Propensity score matching was used to select controls from the CA-only and LAAC-only groups. Each group contained 76 subjects. The procedures were successfully performed in all the patients. Procedure-related complications of the combined group included one pericardial effusion and two groin haematomas, which did not differ significantly with those of the CA-only group (3.9% vs. 2.6%, P=0.650) or the LAAC-only group (3.9% vs. 2.6%, P=0.650), respectively. The AF-free rate of the combined group was comparable with that of the CA-only group after a mean of 2 years follow-up (67.1% vs. 69.7%, P=0.727). Compared with the LAAC-only group, the combined group achieved similar complete occlusion rate at implant (94.7% vs. 93.4%) and at 45 days (82.9% vs. 85.5%). At the end of follow-up, ischemic stroke and bleeding events of the combined group were low (3.9%) and were comparable with those of the CA-only group (5.3%) and the LAAC-only group (2.6%). Conclusions. The combination of AF-CA and LAAC is safe and efficacious compared with single procedures alone.